Cloud Computing : A Practitioner's Guide - Arvind Doss; Rajeev Nanda (New Delhi Mc Graw Hill Education (India) Private Limited, 2013)
This book is targeted to demystify cloud and provide a simple and usable framework to technology practitioners who would want to deliver a cloud-based solution for their enterprise. The authors have attempted to address the needs of a technologist at various levels of the organization, including financial decision makers, executives, architects, designers and the owners of workloads being impacted. The book also discusses the various aspects of adopting a public cloud to host your workload or building an internal cloud in all its flavours-IaaS, PaaS and SaaS implementations. As the book is targeted to all practitioners, it also provides real-time examples of how to create and adopt a hybrid cloud model, which will gain more relevance as this domain matures. The book is also suitable as a course material for students and instructors of Computer Science and IT.The book also includes FAQs on Cloud Computing.
Keywords: Cloud computing